(3OjhGf GdeJfHjs - (3CMeO Hf GdMSjf Hf GdMSf Hf YHO GdUeO Hf GdLYaj Gdchaj GdeJfHj, CHh GdWjH, J (B354 (3g` s ((3OGQ GdSdWfI GdYdjI s)
(3ChdgG (B:s
(3MQa GdCda(B: (3bGd CHhGdWjH, hbO CeQg Sja GdOhdI HELGRI CHjGJ Ydi gPG GdhRf hGdQhi(B: (3YPd GdYhGP Mhd bdHj GdJGFg hghi GdCMHI efg aj ShOGFg s
(3BNQgG (B:s
(3acCfg LjT GHf UaO QYJg MJi cCfc jG Ydj Ydqj s
(3fSNI KGefIs
(3hQO CjVkG JMJ Qbe (B873(3, (B917(3, (B2191(3, (B2195s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B115 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B201s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B196 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B809s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs